Dramaturgy analysis in self-presentation of smokers - Praptiningsih, Novi Andayani; Handayani, Sarah; Agustini, Vilya Dwi (Informasi, 2022)
The purpose of this study was to find out how dramaturgy is in the self-presentation of smokers. The research method uses a qualitative with an interpretive approach. Data collection techniques used in-depth interviews, observations, FGDs, and literature studies. Miles & Huberman interactive model data analysis technique. The results showed that smokers among teenagers almost entirely did dramaturgy where there was a difference in smoking behavior on the front stage and back stage. Smokers apply Goffman's self-presentation, for example on the back stage they smoke, but on the front stage when dealing with teachers/parents/leaders/employers/lover – they do not smoke. The self-presentation of an adult smoker who has fully demonstrated himself as a true smoker places himself on the front stage as well as the back stage, using self-promotional tactics and even exaggeration. However, smokers among teenagers, will make a disclaimer by trying to deny and hide their identity as a smoker if they are at home with their nuclear family, namely father-mother-brother-sister. However, on the back stage, the teen smokers both carried out a self promotion strategy as a technique for presenting themselves by opening themselves up, especially when hanging out with their high-frequency friends.